THE COST OF INNOVATION: EVIDENCE FROM AUDITOR PRICING OF INVENTOR CHIEF EXECUTIVE OFFICERS - Bostan, Ibrahim; Kannan, Yezen H. (International Journal of Accounting & Finance Review, 2021)
The study assesses whether auditors factor into their pricing of an audit engagement the presence of an inventor CEO given the potential conflict of interest this may present. Empirical and anecdotal evidence suggests that inventor CEOs may have more appetite for risk and may be less business-minded, thus suggesting potential agency costs for the firm. We rely on a self-developed database of inventor CEOs and archival data from other sources. Using multivariate regressions, we assess the association between the presence of an inventor CEO and audit fees, while controlling for audit fee determinants. The results of our analysis reveal that auditors assess a fee premium in the presence of inventor CEOs. Additional analysis also finds that this fee premium is not exacerbated by the presence of audit risk, and the engagement of top-tier auditors significantly reduces auditor pricing of the presence of an inventor CEO. Our analysis also shows that the positive and significant association between audit fees and the presence of an inventor CEO is significantly stronger in the presence of greater financial distress. Overall, our findings suggest that auditors factor into their pricing decision the potential conflict of interest between CEO inventor managers and shareholders.JEL Classification Codes: M42, J2, O32.